History in the digital age - Weller, Tom (Routledge/Taylor & Francis Group, 2013)
"The digital age is affecting all aspects of historical study, but much of the existing literature about history in the digital age can be alienating to the traditional historian who does not necessarily value or wish to embrace digital resources. History in the Digital Age takes a more conceptual look at how the digital age is affecting the field of history for both scholars and students. The printed copy, the traditional archive, and analogue research remain key constitute parts for most historians and for many will remain precious and esteemed over digital copies, but there is a real need for historians and students of history to seriously consider some of the conceptual and methodological challenges facing the field of historical inquiry as we enter the twenty-first century" -- Provided by publisher.